ADAPTASI SISTEM KOMUNIKASI PEMERINTAH DALAM PENINGKATAN KUALITAS KAMBING KALIGESING DI PURWOREJO - Tatag Handaka; Hermin Indah Wahyuni; Endang Sulastri; Paulus Wiryono (AGRITEXTS: Journal of Agricultural Extension, 2017)
Population of Kaligesing goat in Purworejo indicates the number continues to increase from year to year. However, increasing in population is not accompanied by an increase in the quality of Kaligesing goat. The objective of the study is to know how adaptation of government communication system on increasing quality of Kaligesing goat in Purworejo regency. The theory of the study is communication system in perspective of Niklas Luhmann. The study was used explorative case study method. Population of this study was conducted in Purworejoregency as the centerof Kaligesing goat farming.The technique of collecting data is using indepth interview and observation. The result of the study showed that government communication system was produce and reproduce information as regulation. Those information was used to solved environment complexity in the form of decreasing of Kaligesing goat quality. Government communication system wasn’t effective on reducting and selecting environment information. So, information was produced by system not solved environment complexity. Government communication system encountering environmental complexity evolved into an unadaptive system.